Designing Public Relations and Public Service Programs to Improve Public Image and Satisfaction - Rochmat Widodo; Taufik Hidayat; Romlah; Ali Abdul Wakhid (Al-Qalam Institue, 2025)
This study examines the design of a Public Relations and public service program aimed at improving institutional image and public satisfaction. Identified problems include a lack of communication integration, public services that are not fully responsive to public needs, and limited transparency and accountability, all of which contribute to low levels of public trust and participation. The purpose of this study is to analyze Public Relations program design strategies, identify community-oriented communication mechanisms and innovations in public services, and assess the role of transparency, accountability, and performance evaluation in strengthening institutional image. The method used is library research with a descriptive-qualitative approach, namely the collection and analysis of literature, journals, books, and documents related to Public Relations, public services, public communication, and institutional management. The results indicate that thorough strategic planning, appropriate communication implementation, responsive public service innovation, and systematic performance evaluation can increase public satisfaction and strengthen institutional image. This research's contribution lies in developing a Public Relations program model integrated with public service systems —both conventional and digital —to increase public trust and strengthen relationships between institutions and the community.